PERBANDINGAN TULANGAN LENTUR PADA GEDUNG FAKULTAS PSIKOLOGI UNIVERSITAS SEMARANG DENGAN MEMBANDINGKAN PERATURAN SNI GEMPA 2012 DENGAN SNI GEMPA 2019 - Crista, Ngudi Hari; Widorini, Trias Nani; Anggraini, Lila Nani (Jurnal Pengembangan Rekayasa dan Teknologi, 2020)
Given the last few years there have been many large earthquakes that have occurred in Indonesia. For example, the Aceh earthquake in 2004, the Yogyakarta earthquake in 2006, the Padang and Bengkulu earthquake in 2007. The earthquake caused a lot of damage to building structures. After conducting an in-depth study on this matter, that the large earthquake that occurred turned out to be due to the acceleration of the bedrock which was greater than the acceleration of the bedrock that had been determined in the SNI 03-1726-2012 earthquake map. Based on these findings, the earthquake map SNI 03-1726-2012 was deemed no longer suitable to be applied as a guideline for earthquake resistant structure planning. Because a new earthquake regulation appeared and was enforced, this resulted in the need for revision or review of existing buildings to be reviewed using the latest regulations. With the existence of the latest regulations (RSNI 03-1726-2019), all buildings planned with the old regulations (SNI 03-1726-2012) need an evaluation of the calculation of the earthquake effect of the old buildings against the latest regulations. Therefore, after conducting research by comparing the structural behavior between the two regulations in the USM psychology faculty lecture building in the T building by comparing SNI 03-1726-2012 with SNI 03-1726-2019, the comparison results obtained in the column of longitudinal reinforcement requirements experienced an increase of 50% and the need for shear reinforcement has increased by 12.04%, while for the comparison of beams the need for longitudinal reinforcement has increased in field reinforcement by 25%, and the shear reinforcement has increased by 25%
Keywords: Comparison of earthquake; Psychology; Flexibility; Shifting SNI 2012 with SNI 2019